Effect of heating rate and additives (MgO and Al2O3) on a diesel like-fuel issued from waste engine oil pyrolysis. (19th May 2019) - Zouad, Y.; Tarabet, L.; Khiari, K.; Mahmoud, R.
Abstract: Pyrolysis experiments were conducted at atmospheric pressure in a batch reactor ranging from room temperature until 420 °C. The suitable heating rate was studied by keeping constant the reaction temperature at several levels (300, 320, 340, 360, 380 and 400 °C) for 60 min. by application the best heating program; MgO and Al2 O3 additives are examined at various proportions (1, 2, 3, 4 and 5% by weight). It has been shown that the addition of MgO (1-2% by wt.) leads to a supplemental improvements in the DLF quality where the properties are the closet to those of conventional diesel fuel.